Loading-dependent mechanical performance of alkali-treated areca nut husk fiber reinforced polyester composites modified with Uncaria gambir extract - Rahmat Azis Nabawi; Syahril Syahril; Hairul Abral (Universitas Negeri Padang, 2025)
Natural fiber-reinforced polymer composites often experience mechanical performance limitations due to weak interfacial bonds between hydrophilic fibers and hydrophobic matrices. This study experimentally examined the effect of alkali treatment and modification using Uncaria gambir extract (UGE) on the mechanical properties and interface morphology of polyester composites reinforced with areca nut husk fiber (ANHF). Four composite configurations were prepared with a constant fiber weight fraction of 40 wt.% after alkali treatment using 6% NaOH for 24 hours, while the remaining 2 wt.% UGE was selectively applied as a fiber surface treatment, matrix additive, or a combination of both. Tensile and flexural properties were evaluated in accordance with ASTM standards, while interface morphology was examined using scanning electron microscopy (SEM). The results showed that alkali-treated composites without UGE addition had the highest tensile strength, which was attributed to increased fiber surface roughness and mechanical interlocking mechanisms. Conversely, fiber surface modification using UGE significantly increased flexural strength, indicating better stress distribution under flexural loading due to increased interface continuity. However, the addition of UGE to the matrix caused a decrease in tensile strength, which was thought to be related to a reduction in matrix stiffness. SEM observations confirm the presence of distinct interface morphology differences according to the treatment applied. These findings indicate that UGE serves primarily as a bio-based interfacial modifier, enhancing flexural performance, while its effectiveness is strongly governed by the mechanical loading mode.